Actuators: Remotely Light‐Powered Soft Fluidic Actuators Based on Plasmonic‐Driven Phase Transitions in Elastic Constraint (Adv. Mater. 51/2019). Issue 51 (17th December 2019) - Meder, Fabian; Naselli, Giovanna Adele; Sadeghi, Ali; Mazzolai, Barbara
Abstract : In article number 1905671, Fabian Meder, Ali Sadeghi, Barbara Mazzolai, and Giovanna Adele Naselli describe a light‐driven soft pump that is based on a phase‐transition‐induced pressure generation of plasmonic nanoparticles constrained in an elastomer. The mechanism combines light‐powering with fluidic actuation for soft actuators in microfluidics and soft robotics.